Dynamic resource allocation scheme for multiuser OFDM–UWB systems based on user's rate - Chao CHENG; Zhi-hong QIAN; Chun-lan LI; Xue WANG (Tongxin xuebao)
According to original dynamic resource allocation algorithms,a new dynamic resource allocation algorithm for multiuser OFDM-UWB system based on users'rates was proposed to minimize the total transmitting power whil sa-tisfy requests for QoS and data rate of all users.Qual ty of the system was improved running the subcarrier allocation and bit allocation algorithms based on fairness of users.In subcarrier allocation process,rate impact factor was used to com-pare influence of different subcarriers to a user.In allocation process,bits were allocated to each user's subcarriers first,then bits on each subcarriers were adjusted according to rate request of each user.In or to reduce the complexity system of the furthermore,a subcarrier and bit allocation scheme is employed through subcarrier grouping.Simulation results indicate that the algorithm can lower power consume,BER and operation complexity.